O trabalho da fisioterapia junto aos trabalhadores com lombalgia crônica: desafios nos processos educativos - Rocha, Fernanda Santos [UNIFESP] (2015)
Aim: To investigate the teaching-learning processes related to postural orientations conducted by the physiotherapy team next to workers with chronic low back pain and retiremente from work situation in Santos region, and the knowledge of team on Permanent Health Education in a worker`s service unit. Methods: An exploratory study, descriptive and qualitative. In three steps. Step 1) invitation os physiotherapists to conduct individual interview with a script that were recorded and integral transcribed for categorial content analysis. Step 2) selected workers patientes, both genders, various professions, through physiotherapy records in the period 1 January to 20 July 2014, as: demographic, phone, profession, if experienced retirement of work situation, profession, among others. The subjects selected through records were invited to attend a meeting in Discussion Group, also the physiotherapists. Step 3) held a meeting for discussion group with the physiotherapy team with a script pre-elaborated and content analyses. Results: next to physiotherapists, occurend frequency of high demands of work, which promote difficulties to give more attention next to patients. Also stigmata next to work retirement situation and the supposed interest to learn, acknowledge of Permanent Health Education and others, that influenced in teaching-learning processes. In Discussion Group evidenced between workers the difficulties to apply the postural orientations out of the therapeutic ambient, fear of the return to work, aggravation of pain and chronic symptoms after the physiotherapy sessions, among others. Final Thoughts: This present study evidenced difficulties next to the teaching-learning process during postural orientations performed by physiotherapists, as well as the lack of information on Permanent Health Education and its applicability in their everyday practices. It´s necessary to understand the various processes involved, review and get better ways and methods to promote educational processes.